Periodic Paralysis and Encephalopathy as Initial Manifestations of Graves' Disease: Case Report and Review of the Literature. Issue 4 (July 2017) - Tsironis, Theocharis; Tychalas, Athanasios; Kiourtidis, Dimitrios; Kountouras, Jannis; Xiromerisiou, Georgia; Rudolf, Jobst; Deretzi, Georgia
Abstract : Background: Thyrotoxic periodic paralysis (TPP) is an uncommon complication of Graves' disease, characterized by the triad of acute hypokalemia without total body potassium deficit, episodic muscle paralysis, and thyrotoxicosis. Graves' encephalopathy is an extremely rare form of encephalopathy associated with autoimmune thyroid disease (EAATD), characterized by neuropsychiatric symptoms, increased antithyroid antibodies and cerebrospinal fluid protein concentration, nonspecific electroencephalogram abnormalities, and cortico-responsiveness. Coexistence of both these complications in the same patient has not been reported before. Case Report: We herein present a 48-year-old white male patient with TPP and encephalopathy as initial presentations of Graves' disease. Flaccid tetraparesis was reversed a few hours after potassium level correction and the patient did not suffer any relapse with the successful pharmaceutical management of the thyroid function. One month later, the patient presented with dizziness and behavioral symptoms, such as inappropriate laughter and anger. Brain magnetic resonance imaging revealed meningeal enhancement and cerebrospinal fluid analysis showed a mild protein increase, with a blood-brain barrier disruption. With the suspicion of EAATD, the patient was treated with high doses of corticosteroids and improved dramatically. Conclusions: To our knowledge this is the first reported coexistence of potentially treatable TPP and EAATD as initial neurological manifestations of Graves' disease, thereby underscoring the necessity of suspicion of possible underlying Graves' disease in patients with acute paralysis and encephalopathy of unclear origin.